Pergeseran Paradigma Pengelolaan Kawasan Konservasi: Sebuah Wacana Baru dalam Pengelolaan Kawasan Konservasi - Soekmadi, Rinekso (Media Konservasi, 2003)
Managing protected area in the proper way is one of the most effective effort to conserve the last tropical biodiversity and ecosystems. Nowaday management of protected area faces to many "threats" from others. With regards to global situation, the way of protected area management has to be adjusted and shifted in line with new paradigm that develop based on lesson learn from best practices in many countries over the world. According to global history, current management of protected area should recognize local needs and must be recognized by local. The existence of protected area must bring significant benefits to multi-stakeholders. We have to broaden mind that protected area is not just the needs of central goverment or conservationists to save our earth, but there should also be an access for others to take real benefits. If it is consistently adopted, however, protected area authority is not the only responsible institution towards conservation of biodiversity within the area.